A Rare Case of Pseudomonas aeruginosa-Associated Diarrhea in a Cirrhotic Patient - Malcolm Chapman; Atul Lodh; Joven Tristeza; Alexander Yang (Case Reports in Hepatology)
While rare, cases of community-acquired Pseudomonas aeruginosa (PsA) enterocolitis have been reported and are associated with recent antibiotic use and immunocompromised hosts. Here we present a 29-year-old immunocompetent female with newly diagnosed alcoholic cirrhosis that presents with bloody diarrhea and was found to have PsA in her stool culture. This case is unique as our patient does not have a history of recent antibiotic use or prior history of immunosuppression. However, immune dysfunction in cirrhosis results in defects in both innate and acquired immunity, thus predisposing our patient to PsA-associated diarrhea. Overall, this case showcases that, while considered immunocompetent, cirrhotic patients are predisposed to rare infections such as PsA in the community due to defects in their immune system.